Bad luck chicken - Baker, Naomi (School of Languages and Literatures, 2024)
He is standing holding a handwritten sign with her name, his flannel shirt tight around the shoulders and unbuttoned at the neck, his blond hair flattened by an invisible cap. Tia wishes she had gone to the bathroom beforehand, brushed her hair, put eye drops in, perhaps lined her lashes with mascara. She can only guess what she looks like after two long-haul flights and eight hours in a fluorescent terminal in Abu Dhabi. Tia knows his name already. Caleb. It is in the slim volunteer packet, which she has read again and again, as if memorizing the words will make her more certain about her decision to travel across the world. It is odd—he is holding her name like he owns her, but he does not know who she is. He glances at the people and their bags hopefully. She could walk right past him. Perhaps she should. Already, through the haze of her fatigue, she feels a jolt of attraction, a sense of a storyline unspooling between them, an inevitability she could avoid by walking past him.